Recombinant Factor VIIa Does not Induce Hypercoagulability In Vitro - Gallistl, Siegfried; Cvirn, Gerhard; Muntean, Wolfgang (Thrombosis and Haemostasis, 1999)
Recombinant factor VIIa (rVIIa) has been reported to be clinically effective and safe in haemophilic patients with inhibitor antibodies. Compared to activated prothrombin complex concentrates the risk of thrombotic complications seems to be very low after rVIIa administration. Determination of free thrombin generation has been shown to identify hypercoagulability. Therefore, free thrombin and prothrombinase activity (Xa generation) were assessed after extrinsic activation of rVIIa supplemented factor VIII and factor IX deficient plasma. Free thrombin generation was also determined after supplementation of (activated) prothrombin complex concentrates. Addition of 150 U rVIIa/ml shortened the clotting times markedly in control, factor VIII, and factor IX deficient plasma. In contrast, free thrombin and Xa generation were not different in the absence or presence of 150 U rVIIa/ml. Addition of (activated) prothrombin complex concentrates resulted in a marked increase of free thrombin generation in all investigated plasmas. Although in vitro studies cannot reflect specific clinical circumstances our results support the notion that rVIIa does not induce a hypercoagulable state as sporadically observed after administration of (activated) prothrombin complex concentrates.